Moral dilemmas in English confessors’ manuals - Corran, E (Boydell & Brewer, 2017)
Cases of conscience are real or imagined moral dilemmas involving a choice between two non-ideal courses of action. Writings on cases of conscience – casuistry - were a feature of Catholic moral philosophy through the early modern period and into the nineteenth century, with a phase of particular notoriety in the mid-seventeenth century. To historians of the Counter-Reformation, casuistry is a familiar concept because of the abundance of writings on practical ethics produced and because the subject of casuistry played a prominent role in religious polemic. When Martin Luther made a bonfire of books he believed to be dangerous to the Christian faith in 1520, he included a popular book of cases of conscience, the Summa Angelica. Blaise Pascal satirised the casuistry of the Jesuits in his Lettres Provinciales. In reformed England in the late sixteenth century, Jesuit evangelists were found to carry small treatises with advice on cases of conscience originating from the seminaries at Douai and Rheims, which were intended to provide moral guidance to Catholics negotiating a complicated path between dissimulation and recusancy. Although casuistry is thus most associated with the social and religious history of the sixteenth century, it was also a common feature of penitential writing in England and Europe in the thirteenth century. Earlier writings on moral cases have attracted much sparser recognition in modern scholarship than their early-modern counterparts, yet they were no less a feature of medieval pastoral treatises, and played just as crucial a role in medieval pastoral care. These medieval moral dilemmas are the subject of this paper; it will argue that their appearance in English confessors’ manuals marked the beginning of a new genre of Catholic moral philosophy. There had, of course, been discussions about applied ethics before the thirteenth century, but this was the first time that there was a sustained interest in the subject, and that it was attached so closely to pastoral care and penitence. The combination of moral dilemmas and penitential advice would later also characterise the collections of cases of conscience in the sixteenth century.